Contribuições para a gestão dos mestrados profissionais: identificação das boas práticas - Barros, Roni Storti de (2016)
In universities today, the administrative positions as heads of department, course coordination, central direction, are occupied by teachers. These professionals act administratively in their areas of training and should play this role in order to satisfy the interests of the course. This study aims to propose a management primer to professional master's courses in Brazil, presenting a more effective insight into the ways of acting courses. The study is focused on the evaluation of the 2010-2012 period, due 2013 by CAPES, where a sample of 17 courses was set in 9 different areas of evaluation, covering private and private institutions. To meet the specific objectives, the description of these areas was carried out, as well as each course, considering the figures, teachers, completed jobs, intellectual production, and other data, also described the main items of the report of the proposal of each of these courses. From there, it made analysis of the area of documents and evaluation reports, list the practices cited by more courses rose concept. Listing the main practices, and checking what is described by most of the courses in their reports. As a result, lists are some actions to be observed, as the correct completion of the proposal by description and focus of research projects, still seeking cooperation agreements. Finally, note that rise concept, the course that stand out from their peers, and carry out activities in order to optimize the formation of his student and improve its publications list.